IGF2 knockdown in two colorectal cancer cell lines decreases survival, adhesion and modulates survival-associated genes - Rogers, Michael A.; Strowitzki, Moritz; Schneider, Martin (Tumor biology, 2016)
Increased expression of insulin-like growth factor 2 (IGF2) is found in tumors of colorectal cancer (CRC) patients exhibiting a gained region on chromosome 11q15 and is implicated in poor patient survival. This study analyzes in vitro phenotypic- and gene expression changes associated with IGF2 shRNA-mediated knockdown. Initially, doxycycline inducible IGF2 knockdown cell lines were generated in the CRC cell lines SW480 and LS174T. The cells were analyzed for changes in proliferation, cell cycle, apoptosis, adhesion, and invasion. Expression profiling analysis was performed, and, for a subset of the identified genes, expression was validated by qRT-PCR and Western blot. IGF2 knockdown inhibited cell proliferation in both cell lines induced G1 cell cycle blockade and decreased adhesion to several extracellular matrix proteins. Knockdown of IGF2 did not alter invasiveness in SW480 cells, while a slight increase in apoptosis was seen only in the LS174T cell line. Knockdown of IGF2 in SW480 deregulated 58 genes, several of which were associated with proliferation and cell-cell/cell-ECM contacts. A subset of these genes, including CDK2, YAP1, and BIRC5 (Survivin), are members of a common network. This study supports the concept of direct autocrine/paracrine tumor cell activation through IGF2 and a shows role of IGF2 in CRC proliferation, adhesion and, to a limited extent, apoptosis.